2017
DOI: 10.5455/ijtrr.000000279
|View full text |Cite
|
Sign up to set email alerts
|

Multiple choice questions exams: Guiding principles to develop exam designing skills among novice and inexperienced academics

Abstract: Context

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…A package of tools, including but is not limited to, MCQs checklist (Table I), SELF evaluation strategy diagram (Figure 1), global test blueprint (Table 2), Dr. El-gohary blueprint matrix (Appendix I), in addition to difficulty and discrimination index template (Appendix II) were introduced to academics. [2][3][4] A series of training sessions were carried out over eight-week period. A total of nine academics who participated in the current study were instructed to choose one of their core courses and gradually step by step apply the included academic tools and consult Dr. El-gohary to amend any incorrect items.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A package of tools, including but is not limited to, MCQs checklist (Table I), SELF evaluation strategy diagram (Figure 1), global test blueprint (Table 2), Dr. El-gohary blueprint matrix (Appendix I), in addition to difficulty and discrimination index template (Appendix II) were introduced to academics. [2][3][4] A series of training sessions were carried out over eight-week period. A total of nine academics who participated in the current study were instructed to choose one of their core courses and gradually step by step apply the included academic tools and consult Dr. El-gohary to amend any incorrect items.…”
Section: Methodsmentioning
confidence: 99%
“…1 Academics are facing huge challenge starting from designing academic courses, teaching the related topics, and ending with designing robust exams that capable of discriminating more capable from less capable learners. [2][3][4][5][6] It is unknown if academics visit specific sources to make sure that the exams questions have satisfied the psychometric measures necessary to administer the multiple choice questions (MCQs) exams with full faith. 7 There is a gap in the body of knowledge regarding having specific predesigned templates that can be directly used by academics to design robust MCQs exams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] Academics participated in this study indicated that there is scarcity of feasible template that would be a quick guide when developing the blueprint for their educational subjects. Academics added that using the blueprint is axial to standardize and establish all psychometric measures of the MCQs exams.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,21,22 There is consensus among academics that the level of difficulty should be considered when designing the blueprint since the objectives needed from courses taught at early years of study emphasizes on knowledge acquisition while the objectives at the end of the program emphasizes on critical thinking skills. 12,13,23,24 Therefore, the MCQs exam should have a higher percentage of questions in the analysisevaluation and evaluation-synthesis spectrum. 25,27 Higher levels of critical thinking are the core of developing not only competence but capability as well in the ever changing health field but it needs intensive training from academics.…”
Section: Discussionmentioning
confidence: 99%